2016
DOI: 10.1021/jacs.6b04319
|View full text |Cite
|
Sign up to set email alerts
|

Mg(PF6)2-Based Electrolyte Systems: Understanding Electrolyte–Electrode Interactions for the Development of Mg-Ion Batteries

Abstract: Mg(PF6)2-based electrolytes for Mg-ion batteries have not received the same attention as the analogous LiPF6-based electrolytes used in most Li-ion cells owing to the perception that the PF6(-) anion decomposes on and passivates Mg electrodes. No synthesis of the Mg(PF6)2 salt has been reported, nor have its solutions been studied electrochemically. Here, we report the synthesis of the complex Mg(PF6)2(CH3CN)6 and its solution-state electrochemistry. Solutions of Mg(PF6)2(CH3CN)6 in CH3CN and CH3CN/THF mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 28 publications
4
100
0
4
Order By: Relevance
“…has demonstrated the simple,c ommercially available salt magnesium(II) bis(trifluoromethanesulfonyl)imide( Mg(TFSI) 2 )w hen dissolved in glyme based solvents undergoes magnesium deposition and dissolution. [62] Theo verpotential value negatively affects the energy density in abattery by lowering the discharge battery voltage and increasing the charging voltage.A ssuming am agnesium battery would discharge at 2.5 Vand charge at 3V with zero overpotential, the same battery would have adischarge voltage of 1Vand charge at 5Vif the electrolyte has an overpotential of 2Vat the operating current density. [58] Thee lectrochemical performance of Mg-(TFSI) 2 can be improved by the addition of MgCl 2 which is shown to increase both the current density and the coulombic efficiency of reversible magnesium deposition as the fraction of the magnesium chloride increases.H owever,t he addition of this magnesium chloride will presumably render this electrolyte corrosive in nature.…”
Section: Commercial Saltsmentioning
confidence: 99%
“…has demonstrated the simple,c ommercially available salt magnesium(II) bis(trifluoromethanesulfonyl)imide( Mg(TFSI) 2 )w hen dissolved in glyme based solvents undergoes magnesium deposition and dissolution. [62] Theo verpotential value negatively affects the energy density in abattery by lowering the discharge battery voltage and increasing the charging voltage.A ssuming am agnesium battery would discharge at 2.5 Vand charge at 3V with zero overpotential, the same battery would have adischarge voltage of 1Vand charge at 5Vif the electrolyte has an overpotential of 2Vat the operating current density. [58] Thee lectrochemical performance of Mg-(TFSI) 2 can be improved by the addition of MgCl 2 which is shown to increase both the current density and the coulombic efficiency of reversible magnesium deposition as the fraction of the magnesium chloride increases.H owever,t he addition of this magnesium chloride will presumably render this electrolyte corrosive in nature.…”
Section: Commercial Saltsmentioning
confidence: 99%
“…[41][42][43] These studies showed that modified structures would lead to high magnesium plating efficiencies with higher potential windows. [45] This Mg(BH 4 ) 2 electrolyte wasf urthera pplied in af ull cell containing TiO 2 as the cathode material,Mg(BH 4 ) 2 /LiBH 4 /tetraglyme as the electrolyte, and magnesium metal as the anode.T he cell with an operating voltage of 0.9 Vv ersus Mg/Mg 2 + and capacity of 150 mA h À1 g À1 can stably run for 90 cycles. [44] In an electrolyte composed of 0.5 m Mg(BH 4 ) 2 /diglyme, the magnesium plating efficiency can reach 94 %.…”
Section: Magnesiummentioning
confidence: 99%
“…[1][2][3][4] Particularly, inorganic Mg electrolytes are very scarce. [14][15][16][17][18][19] In previous studies, the MgCl 2 /AlCl 3 electrolytes (called Magnesium and Aluminum Chloride Complex electrolytes, abbreviated as MACC electrolytes), represent the first generation of all inorganic Mg 2+ electrolytes and their simplicity is highly attractive for rechargeable Mg battery applications. 14,15 The MACC electrolytes exhibited good reversibility of Mg deposition/stripping (up to 100% Coulombic efficiency), high anodic stability (up to 3.4 V vs Mg), and limited nucleophilic susceptibility (non-nucleophilic and sulfur compatible).…”
mentioning
confidence: 99%